Popular and useful learning strategies in language acquisition amongst teenagers - Erla Edvardsdóttir (2010)
This thesis examines which learning techniques and strategies teenagers in Iceland prefer to use when it comes to vocabulary acquisition in English and Icelandic both at home and in school, and if any of these strategies seem to work better than others and why. It also looks at the benefits that teaching and training learners in learning strategies bring to both students and teachers and how such training might be best conducted at compulsory school level. A pilot study was undertaken in one local school during October 2009 and after minor changes to the questionnaire it was put to students in 9th and 10th grade at two schools in the capital area during February 2010.